Factors Correlating to Burnout among Otolaryngology Residents. (June 2020) - Reed, Leighton; Mamidala, Madhu; Stocks, Rosemary; Sheyn, Anthony
Objectives: Physicians have high rates of burnout with an Otolaryngology burnout rate of 42%. The most studied burnout correlation is increased work hours. More recently, mindfulness training programs have been shown to decrease burnout and increase self-compassion. Regarding burnout studies specific to Otolaryngology residents, there have been few in the past decade. This study explores correlations between burnout and procedure involvement, non-clinical responsibilities and mindfulness practices along with gathering updated work hours data. Methods: A single survey question was shown to be a reliable substitute for Maslach Burnout Inventory in assessing burnout. A survey was sent to all US Otolaryngology residents to investigate the correlation of burnout to post-graduate year, work hours, procedure involvement, non-clinical responsibilities, and mindfulness practices. Residents were asked to answer questions regarding their previous year of training. Results: Overall burnout was 50%. PGY-1 and PGY-5 were completed with a low burnout rate compared to other years. Increased work hours were confirmed to increase burnout. Increased involvement in procedures, decreased exercise, and increased time completing paperwork correlated with increased burnout. No other factors including mindfulness correlated with increased or decreased burnout. However, only 20% who practiced mindfulness training had this training offered by their department or university. Conclusion: Annals of Otology, Rhinology & Laryngology A 50% burnout rate is a concerning rate. Increased work hours and PGY-2 through PGY-4 correlated with increased burnout. Accessibility to mindfulness training was low. As mindfulness training is a proven activity to decrease burnout, more departments could benefit from providing these experiences to their residents.